2020
DOI: 10.1097/pas.0000000000001478
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of Endometrioid Ovarian Carcinoma

Abstract: Endometrioid ovarian carcinoma (EOC) has clinical and biological differences compared with other histologic types of ovarian carcinomas, but it shares morphologic and molecular features with endometrioid endometrial carcinoma. To analyze the molecular heterogeneity of EOC according to the new molecular classification of endometrial cancer and to evaluate the prognostic significance of this molecular classification, we have analyzed 166 early-stage EOC by immunohistochemistry for mismatch repair proteins and p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…By comparison, efforts to apply the endometrial carcinoma molecular classifier—the PROMISE algorithm—have not identified a sizeable proportion of excellent prognosis EnOC patients 20 22 ; POLE -mutated tumours are reportedly associated with around 90% 10-year overall patient survival, but account for only 3.5% of cases, limiting implementation of POLE as a prognostic marker. Moreover, two of the four subtypes identified by this algorithm—the MMRd and NSMP groups—account for around 85% of cases and demonstrate equivalent clinical behaviour 21 , limiting the utility of this classification system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By comparison, efforts to apply the endometrial carcinoma molecular classifier—the PROMISE algorithm—have not identified a sizeable proportion of excellent prognosis EnOC patients 20 22 ; POLE -mutated tumours are reportedly associated with around 90% 10-year overall patient survival, but account for only 3.5% of cases, limiting implementation of POLE as a prognostic marker. Moreover, two of the four subtypes identified by this algorithm—the MMRd and NSMP groups—account for around 85% of cases and demonstrate equivalent clinical behaviour 21 , limiting the utility of this classification system.…”
Section: Discussionmentioning
confidence: 99%
“…Though this study did not use routine WT1 IHC to exclude potential HGSOC cases, these data suggest the existence of a true EnOC subgroup with genomic features redolent of HGSOC. Moreover, recent IHC-based studies have identified aberrant p53 expression patterns, indicative of TP53 mutation, in 10–24% of cases 20 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serous tumor markers such as WT1, P53, CK20, and mucinous tumor markers such as CEA and MUC2 are not often expressed in EOVC and OCCC, and EOVC-specific 2). In addition, tumors of the POLEmut and MMRd groups were less frequent in EOVC compared with those in EC (95,96,101). The distinction in the proportion of molecular classifications also reflects different microenvironments to some extent.…”
Section: Molecular Characteristics Of Eovcmentioning
confidence: 94%
“…EOVC patients with TP53 abnormalities had a higher frequency of poorly differentiated cells (G2/G3) ( 95) compared with other molecular types and have the worst prognosis. Research has reported that EOVC with abnormal TP53 may be the result of CTNNB1 mutation (95).…”
Section: Cn-high Group (Tp53 Abnormal)mentioning
confidence: 99%